Language Strategies and Language Preferences in the Russian Tertiary Sector, the International Trade and the Impact of the One Belt One Road Initiative - Zhao, Yue (Lingua : Journal of Linguistics and Language, 2025)
While trade policies are important for international trade, the significance of the link between language and trade cannot be ignored. Understanding the language dimensions of trade is essential for assessing the broader impact of the One Belt One Road Initiative (OBORI). This study aims to: (1) analyse the perceived influence of the OBORI on China and Russia; (2) examine the current status of language strategies by both countries within the OBORI’s multilingual framework; and (3) explore the strategic link between language and international exchange, particularly through language strategies. Questionnaire data from Russian university students were analysed to assess preferences for English and Chinese language courses. The findings suggest that both languages are poised for continued relevance in the context of the OBORI in Russia. As China deepens its engagement with the OBORI, graduates with proficiency in Chinese language and cultural literacy will be increasingly sought after—especially within Russian institutions and industries. The results indicate that the growing importance of Chinese language in Russia’s tertiary sector, with long-term implications for international collaboration, trade readiness, and cultural diplomacy.